Revolusi Ilmiah dalam Penentuan Awal Ramadhan: Studi Perbandingan Hisab dan Rukyah Teleskopik Berdasarkan Teori Thomas Kuhn - Nur, Yahya Muhaimin; Yuwono, Adhimas Alifian (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The purpose of this study is to reveal and analyse the methods of rukyatul hilal and hisab in determining the beginning of Ramadan through the perspective of Thomas Kuhn's scientific revolution. The study uses a literature review method with data collection techniques in the form of book reviews, journals, scientific articles, and online sources that discuss both methods and Kuhn's scientific revolution theory. The collected data were then analysed using a qualitative descriptive-analytical approach to identify patterns of paradigm shifts in the context of determining the start of Ramadan. The research findings confirm that rukyatul hilal, despite modernisation through the use of telescopes, remains part of the old paradigm focused on physical observation of the crescent moon as a marker for the start of the month. This modernisation does not alter the fundamental principles of the rukyat paradigm but merely enhances the accuracy of observations through technology. Conversely, the hisab method represents a new paradigm that fundamentally replaces the old paradigm. Hisab employs scientific and accountable astronomical calculations, addressing anomalies and crises arising from the rukyat paradigm, such as observational limitations due to weather conditions. Thus, hisab represents a scientific revolution within Thomas Kuhn's framework, as it shifts the old paradigm with a more systematic and rational approach. This research demonstrates how the integration of science and technology in religious practice can be understood as a revolutionary paradigm shift, while also affirming the close connection between Islam and the development of modern science.